Neuroradiology cases - Eskey, Clifford J. (New York : Oxford University Press, 2012)
Designed for both in-depth study as well as quick reference'Neuroradiology Cases' covers the field of brain imaging through 192 concise and clinically relevant cases.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Nervous system -- Radiography -- Case studies